Hepcidin mRNA levels in mouse liver respond to inhibition of erythropoiesis - Vokurka, M; Krijt, J; Sulc, K; Necas, E (Physiological research, 2006)
Hepcidin, a key regulator of iron metabolism, decreases intestinal absorption of iron and its release from macrophages. Iron, anemia, hypoxia, and inflammation were reported to influence hepcidin expression. To investigate regulation of the expression of hepcidin and other iron-related genes, we manipulated erythropoietic activity in mice. Erythropoiesis was inhibited by irradiation or posttransfusion polycythemia and stimulated by phenylhydrazine administration and erythropoietin. Gene expression of hepcidin and other iron-related genes (hemojuvelin, DMT1, ferroportin, transferrin receptors, ferritin) in the liver was measured by the real-time polymerase chain reaction. Hepcidin expression increased despite severe anemia when hematopoiesis was inhibited by irradiation. Suppression of erythropoiesis by posttransfusion polycythemia or irradiation also increased hepcidin mRNA levels. Compensated hemolysis induced by repeated phenylhydrazine administration did not change hepcidin expression. The decrease caused by exogenous erythropoeitin was blocked by postirradiation bone marrow suppression. The hemolysis and anemia decrease hepcidin expression only when erythropoiesis is functional; on the other hand, if erythropoiesis is blocked, even severe anemia does not lead to a decrease of hepcidin expression, which is indeed increased. We propose that hepcidin is exclusively sensitive to iron utilization for erythropoiesis and hepatocyte iron balance, and these changes are not sensed by other genes involved in the control of iron metabolism in the liver.
Keywords: Antimicrobial Cationic Peptides; proteiny přenášející kationty; GPI-Linked Proteins; Hemochromatosis Protein; Erythropoiesis; Gamma Rays; ferritiny; hepcidiny; Reverse Transcriptase Polymerase Chain Reaction; membránové proteiny; receptory transferinu; Cation Transport Proteins; Erythropoietin; Membrane Proteins; Mice; zvířata; kationické antimikrobiální peptidy; Polycythemia; messenger RNA; regulace genové exprese; fenylhydraziny; polycytemie; Gene Expression Regulation; Time Factors; Ferroportin; sloučeniny železa; mužské pohlaví; hemolytické anemie; Hemolysis; hemolýza; polymerázová řetězová reakce s reverzní transkripcí; Hepcidins; ferroportin; Phenylhydrazines; záření gama; časové faktory; Ferritins; GPI-vázané proteiny; myši; Liver; Animals; RNA, Messenger; Mice, Inbred C57BL; Iron Compounds; erythropoetin; erytropoéza; Anemia, Hemolytic; Receptors, Transferrin; játra; Male; protein hemochromatózy; myši inbrední C57BL